APLIKASI DONASI BERBASIS MOBILE MENGGUNAKAN METODE SCRUM - Habibah, Ariska Nurul; Waluyo, Retno; Jefri Prayitno Bangkit Saputra, (Nusantara Hasana Journal, 2024)
The donation application creates innovative solutions in the world of charity and charity with a design that focuses on an immersive user experience. In Indonesia, there are many online donation applications, but most of the donations given are in the form of money. Apart from money, victims of natural disasters also need assistance in the form of primary goods to meet their basic needs. Given these problems, the "Good Hands" application became a solution and was designed using the Scrum Framework method by determining User Story, Sprint Backlog, Planning, Implementation, Review, Retrospect, and Definition of Done. By incorporating the Scrum framework as a design method, this application not only creates a charity platform but also builds a deep and meaningful experience for each user. The Scrum Framework method is used as the main approach in designing the user interface (UI) and user experience (UX) of this application. This research aims to understand the context and challenges in the world of donations, exploring users' feelings, hopes, and experiences in making donations. The result of this research is a mobile-based donation application with the aim of being an intermediary for donors who will give some of their sustenance to those who need it more.